Znaczenie premiowania dla skutecznej realizacji kosztowej i motywacyjnej funkcji płacy - Kopertyńska, Maria Wanda (The Importance of Bonus in the Overall Realization of Company's Financial and Motivational Strategy, 2008)
The article shows the importance of bonus in the overall realization of company's financial and motivational strategy as applied to work functions. It shows that this type of incentive motivates employees to effective work and certain behaviours. Bonuses also play a big factor in the cost function The effective usage of this type of adjustement to the overall compensation guarantees returns on the applied investments on the workforce. On the other hand, it also guarantees rationalization of financial expenses according to achieved work effects. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 84-92